Uncertainty quantification of electromagnetic devices, circuits, and systems - Roy, Sourajeet (Institution of Engineering & Technology, 2021)
This book focuses on the advances made in the topic of uncertainty quantification (UQ) and stochastic analysis for the design of electromagnetic devices, circuits and systems. It covers the recent explosion in surrogate modelling (metamodeling) techniques for numerically efficient UQ - an attractive, efficient, and popular approach
Keywords: Uncertainty (Information theory) -- Mathematical models.; Stochastic analysis.; Electromagnetic devices -- Design and construction.; elektronické knihy; electronic books